Higher Efficiency of Motion Estimation Methods - Gamcova, Maria; Marchevsky, Stanislav; Gamec, Jan (Radioengineering Society, 2004)
This paper presents a new motion estimation algorithm to improve the performance of the existing searching algorithms at a relative low computational cost. We try to amend the incorrect and/or inaccurate estimate of motion with higher precision by using adaptive weighted median filtering and its modifications. The median filter is well-known. A more general filter, called the Adaptively Weighted Median Filter (AWM), of which the median filter is a special case, is described. The submitted modifications conditionally use the AWM and full search algorithm (FSA). Simulation results show that the proposed technique can efficiently improve the motion estimation performance.
Keywords: Motion estimation; Median filtering; Adaptive weigh-ted median